CRISPR-based suppression drives for vector control - Crisanti, Andrea (Henry Stewart Talks, 2021)
The malaria problem and the mosquito vector, Spreading a genetic modification in a population, The molecular mechanism of gene drive, Gene drive for population control, Efficiency of CRISPR-based gene drives, Gene drive disruption of mosquito fertility genes, Targeting the doublesex gene leading to population suppression without development of resistance